Characterization of the gut‐liver‐muscle axis in cirrhotic patients with sarcopenia. (25th March 2021) - Ponziani, Francesca Romana; Picca, Anna; Marzetti, Emanuele; Calvani, Riccardo; Conta, Giorgia; Del Chierico, Federica; Capuani, Giorgio; Faccia, Mariella; Fianchi, Francesca; Funaro, Barbara; Josè Coelho‐Junior, Helio; Petito, Valentina; et al.
Abstract: Background & Aim: Sarcopenia is frequent in cirrhosis and is associated with unfavourable outcomes. The role of the gut‐liver‐muscle axis in this setting has been poorly investigated. The aim of this study was to identify gut microbiota, metabolic and inflammatory signatures associated with sarcopenia in cirrhotic patients. Methods: Fifty cirrhotic patients assessed for the presence of sarcopenia by the quantification of muscle mass and strength were compared with age‐ and sex‐matched controls. A multiomic analysis, including gut microbiota composition and metabolomics, serum myokines and systemic and intestinal inflammatory mediators, was performed. Results: The gut microbiota of sarcopenic cirrhotic patients was poor in bacteria associated with physical function ( Methanobrevibacter, Prevotella and Akkermansia ), and was enriched in Eggerthella, a gut microbial marker of frailty. The abundance of potentially pathogenic bacteria, such as Klebsiella, was also increased, to the detriment of autochthonous ones. Sarcopenia was associated with elevated serum levels of pro‐inflammatory mediators and of fibroblast growth factor 21 (FGF21) in cirrhotic patients. Gut microbiota metabolic pathways involved in amino acid, protein and branched‐chain amino acid metabolism were up‐regulated, in addition to ethanol, trimethylamine and dimethylamine production. Correlation networks and clusters of variables associated with sarcopenia were identified, including one centred on Klebsiella /ethanol/FGF21/ Eggerthella / Prevotella . Conclusions: Alterations in the gut‐liver‐muscle axis are associated with sarcopenia in patients with cirrhosis. Detrimental but also compensatory functions are involved in this complex network.